Comparison of the clinical chemistry score to other biomarker algorithms for rapid rule-out of acute myocardial infarction and risk stratification in patients with suspected acute coronary syndrome - Yildirim, Mustafa; Salbach, Christian; Reich, Christoph; Milles, Barbara Ruth; Biener, Moritz; Frey, Norbert; Giannitsis, Evangelos; Müller-Hennessen, Matthias (International journal of cardiology, 2024)
Background - The clinical chemistry score (CCS) comprising high-sensitivity cardiac troponins (hs-cTn), glucose and estimated glomerular filtration rate has been previously validated with superior accuracy for detection and risk stratification of acute myocardial infarction (AMI) compared to hs-cTn alone. - Methods - The CCS was compared to other biomarker-based algorithms for rapid rule-out and prognostication of AMI including the hs-cTnT limit-of-blank (LOB, <3 ng/L) or limit-of-detection (LOD, <5 ng/L) and a dual marker strategy (DMS) (copeptin <10 pmol/L and hs-cTnT ≤14 ng/L) in 1506 emergency department (ED) patients with symptoms suggestive of acute coronary syndrome. Negative predictive values (NPV) and sensitivities for AMI rule-out, and 12-month combined endpoint rates encompassing mortality, myocardial re-infarction, as well as stroke were assessed. - Results - NPVs of 100% (95% CI: 98.3-100%) were observed for CCS = 0, hs-cTnT LoB and hs-cTnT LoD with rule-out efficacies of 11.1%, 7.6% and 18.3% as well as specificities of 13.0% (95% CI: 9.9-16.6%), 8.8% (95% CI: 7.3-10.5%) and 21.4% (95% CI: 19.2-23.8%), respectively. A CCS ≤ 1 achieved a rule-out in 32.2% of all patients with a NPV of 99.6% (95% CI: 98.4-99.9%) and specificity of 37.4% (95% CI: 34.2-40.5%) compared to a rule-out efficacy of 51.2%, NPV of 99.0 (95% CI: 98.0-99.5) and specificity of 59.7% (95% CI: 57.0-62.4%) for the DMS. Rates of the combined end-point of death/AMI within 30 days ranged between 0.0% and 0.7% for all fast-rule-out protocols. - Conclusions - The CCS ensures reliable AMI rule-out with low short and long-term outcome rates for a specific ED patient subset. However, compared to a single or dual biomarker strategy, the CCS displays reduced efficacy and specificity, limiting its clinical utility.